Pengaruh Transparansi dan Kualitas Pelayanan Terhadap Keputusan Muzakki Membayar Zakat di BAZNAS Kabupaten Kepualauan Meranti - Lilis Susanti; Grandis Imama Hendra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to identify how Transparency and Service Quality influence Muzakki's decisions to pay Zakat at Baznas Kabupaten Kepulauan Meranti. Data in this study is processed using quantitative analysis through the partial least square (PLS) approach in the Structural Equation Model (SEM), utilizing the statistical software SmartPLS 3.0. The data collection instrument was a Likert scale questionnaire. The research sample was taken using non-probability sampling method, with purposive sampling technique, resulting in 150 respondents from Muzakki in Kabupaten Kepulauan Meranti.The results of this study indicate that the transparency towards Muzakki's decision to pay zakat on the path coefficients with the original sample value of 0.129 means it has a positive effect with the t-statistic value obtained of 1.278 with a p-values value of 0.202 which is greater than 0.05, thus having a non-significant effect. The service quality variable has a positive and significant effect on Muzakki's decision to pay Zakat at Baznas Kabupaten Kepulauan Meranti. The transparency and service quality variables together have a simultaneous influence on Muzakki's decision to pay Zakat by 47%, while the remaining 53% is explained by other external variables not investigated in this study.